Changing Role of Industry in the Economy in the V4 Countries – a Regional Approach - Kilar, Wioletta; Rachwal, Tomasz (Theory, Methodology, Practice – Review of Business and Management, 2014)
The theme of the article is the changing role of industry in the economy of the countries of the Visegrád Group, further referred to as V4. The goal of the research is to delimit the regularities in terms of changes of the importance of industrial activity in the economy of the region in the conditions of moving from the industrial to post-industrial to information phase of the development and building of a knowledge-based economy. The analysis is based on the NUTS-2 regions of the V4 countries against the general changes in the European Union states, based on selected measurements of industrial potential, i.e. employment and gross value added of industry, as well as indicators of spatial concentration, structure and dynamics in industrial activity, with a special focus on those related to the knowledge-based economy, such as employment in technology and knowledge-intensive sectors. The analysis is dynamic and refers to the years 2000-2012. The research is based on the following methods: comparative analysis, explanation, quantitative analysis and cartographic analysis, all with a regional approach. The analysis indicates the diminishing role of industry in the V4 countries compared to the other EU states. However, the participation of employment in industry is relatively high in comparison with the rest of the EU states. Concentration of industry occurs in the earlier developed areas of concentration, i.e. industrial districts. As a result, there is a need for a new interpretation of the regional policy in the V4 states, where more attention should be paid to the role of industry in shaping the economic structure.